Hovden Food Products Corp. Cannery Employment Office - Richard L. Allman:::Creator::::::::::::
Hovden Food Products cannery building at the northwest end of Cannery Row. The View is of a side corner of building with a power pole center sign, reading: 'Hovden Food Products Corp. Cannery Employment Office.' RESTRICTED USE